[PS 01-26] THE ROLE OF ACTIVATED RENIN-ANGIOTENSIN SYSTEM FOR THE MRP8/TLR4 SIGNALING IN DIABETIC NEPHROPATHY. (September 2016) - Umemoto, Shuro; Kuwabara, Takashige; Imamaki, Hirotaka; Hayata, Manabu; Izumi, Yuichiro; Kakizoe, Yutaka; Mori, Kiyoshi; Mukoyama, Masashi
Abstract : Objective: We previously reported that myeloid-related protein 8 (MRP8: S100A8) / toll-like receptor 4 (TLR4) signaling activated by macrophage (Mφ)-mediated glucolipotoxicity might play an important role in the progression of diabetic nephropathy. Although local activation of the renin-angiotensin system (RAS) in the kidney has been observed in concurrence with the MRP8/TLR4 activation in the diabetic-hyperlipidemic model mice, the relationship between these signals is unknown. Design and Method: In vivo, diabetic-hyperlipidemic mice by STZ plus high-fat diet (STZ-HFD mice) or db/db mice were treated with an angiotensin-receptor blocker olmesartan (Olm, 0.5 microg/kg/min, 4wk) or angiotensin II (AngII, 0.3 microg/kg/min, 2wk), respectively. In vitro, Mφ was stimulated with mesangial cell-conditioned medium (Mes-sup) with or without a TLR4 antagonist. Expression of MRP8 mRNA and inflammatory pathway in detail were evaluated with TaqMan real-time PCR and THP1-dual reporter cell line, respectively. Results: Angiotensinogen (Agt) mRNA was locally upregulated in the glomeruli of STZ-HFD mice, whose changes also occurred in TLR4 knockout mice. Olm effectively suppressed upregulation of glomerular MRP8/TLR4 and Agt in STZ-HFD mice, which were associated with reduction of albuminuria, Mφ infiltration and proinflammatory/profibrotic gene expressions in the kidney. Besides, a subpressor dose of AngII markedly worsened albuminuria and increased glomerular infiltrated MRP8-positive cells in db/db mice. Since glomerular infiltrated Mφ showed obviously high MRP8 positivity compared to tubulointerstitial Mφ, we speculated the intraglomerular crosstalk between Mφ and glomerular intrinsic cells. Mes-sup stimulation, rather than proximal tubular cell-conditioned medium, potently induced MRP8 expression and also interferon regulatory factor (IRF)-pathway, which could cause the ER stress, in Mφ. This induction was partially abrogated by the TLR4 antagonist. Conclusions: RAS activation in diabetic kidney could contribute to progression of nephropathy through promoting intraglomerular crosstalk, which may trigger MRP8 production in glomerular infiltrated Mφ.